A PRAGMATIC ANALYSIS ON METAPHORS IN CIGARETTE ADVERTISEMENTS - Rahman, O. Suzana (Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
The title of this research is : A PRAGMATIC ANALYSIS ON METAPHORS ON CIGARETTE ADVERTISEMENTS. The objective of this study is to analyse the use of metaphor in cigarette advertisement in the view off pragmatic. This is due to the cigarette advertisement is not allowed to advertise their products because cigarette is very dangerous for the cobsumerâs health. Therefore, the advertisers use metaphors to hide the real meanings. Thus, teenagers or youths will find difficulties in interpreting the meanings of metaphors used in cigarettes advertisement. This is qualitative research, therefore, it uses descriptive methods using the theories of Yuleâs, Levinsonâs, and Thomas. Yulesâs and Thomas describe about the functions of the illocutionary force of the speech acts; while Nielson and Storik describe the classification of metaphors, added by Levinsonâs theory that describes about kinds of metaphors and the way too interpret their meanings. After the analysis was executed, the writer found that directives and reoresentatives are mostly used in cigarette advertisement, while in the classification of metaphors, personification are mostly used and kind of metaphors that are mostly used in cigarette advertisement are nominal metaphors. Kata kunci : metafor, advertisement, speech acts,locution, illocutionary, perlocutinary acts.